Nonlinear Dynamics Analysis of Subway Gear Transmission System with Fault Parameter - Sun Ran; Yang Jianwei; Wu Huijie (Jixie chuandong)
The helical gear is an important form of transmission in subway vehicles,helical gear failure has a great impact on the subway operation. In order to investigate the influence of fault parameters on the nonlinear dynamics of metro gear system,the stiffness failure and tooth surface fault parameters of 6-DOF subway bending-torsion-shaft coupling mode are established,by using the variable step fourth-order Runge-Kutta numerical integration method the gear dynamics model with fault parameters is analyzed to get the dynamic response process of the system. With the system status judgment criteria of speed-time process graph,phase plane graph,Poincare cross-section graph and bifurcation diagram,the system excitation frequency,the evolution of system periodic motion,quasi-periodic motion and chaotic motion with fault parameters changing are qualitatively analyzed. The results show that the failure parameters have different effects at different speeds.